2017
DOI: 10.1016/j.jss.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate as a molecular mediator of the vascular response to injury

Abstract: Background Human saphenous veins used for arterial bypass undergo stretch injury at the time of harvest and pre-implant preparation. Vascular injury promotes intimal hyperplasia, the leading cause of graft failure, but the molecular events leading to this response are largely unknown. This study investigated adenosine triphosphate (ATP) as a potential molecular mediator in the vascular response to stretch injury, and the downstream effects of the purinergic receptor, P2X7R, and p38 MAPK activation. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…ATP is normally retained within the cytoplasm and a steep ATP concentration gradient exists between the cytoplasm (10 −3 to10 -2 M) [ 27 ] and the extracellular space (10 −9 to 10 −8 M) [ 36 ]. Thus, tissue damage would lead to rapid release of high local concentrations of ATP consistent with the concentrations of eATP used in this study [ 37 , 38 ].We have demonstrated earlier that stretch injury is associated with ATP release, P2X7R activation, and decreased contractile function in RA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP is normally retained within the cytoplasm and a steep ATP concentration gradient exists between the cytoplasm (10 −3 to10 -2 M) [ 27 ] and the extracellular space (10 −9 to 10 −8 M) [ 36 ]. Thus, tissue damage would lead to rapid release of high local concentrations of ATP consistent with the concentrations of eATP used in this study [ 37 , 38 ].We have demonstrated earlier that stretch injury is associated with ATP release, P2X7R activation, and decreased contractile function in RA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed rat aorta (RA) model of subfailure overstretch injury showed that vascular stretch injury led to impaired contractile function that also was partially restored with inhibitors of P2X7R [ 11 , 19 ]. Since subfailure overstretch injury was associated with release of ATP in rat aorta [ 20 ] and FCF, a P2X7R inhibitor restored vasomotor dysfunction after stretch injury, P2X7R activation is postulated to play a role in stretch injury of vascular tissue.…”
Section: Introductionmentioning
confidence: 99%
“…As ATP is released into the bloodstream as a vascular response to stress or injury, its signalling function is particularly relevant in pathologies related to blood vessels [143]. Red blood cells (RBCs) modulate vasodilation by releasing ATP when oxygen concentrations decrease [144,145].…”
Section: Pathologies Related To Blood Vesselsmentioning
confidence: 99%
“…The P2X7 receptor (P2X7R), which primarily acts via NLRP3 inflammasome‐mediated signaling, has been shown to be critical for bacterial killing in monocytes and macrophages (Csoka et al, 2015 ; Hill et al, 2010 ), but the role of P2X7R on the endothelium during sepsis has not been well characterized. Our group previously showed that activation of P2X7R leads to impaired endothelial‐dependent relaxation in response to stretch injury (Guth et al, 2017 ; Komalavilas et al, 2017 ; Luo et al, 2016 , 2017 ), exogenous ATP stimulation (Guth et al, 2017 ; Komalavilas et al, 2017 ), and acidic normal saline solutions (Cheung‐Flynn et al, 2019 ). Additionally, other groups have identified a protective role for P2X7R antagonism in several experimental models of sepsis (Arulkumaran et al, 2018 ; Santana et al, 2015 ; Savio et al, 2017 ; Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%